Traditional Institution Performance in Engagement Cancellation Customs: Kinerja Lembaga Tradisional dalam Kebiasaan Pembatalan Perjanjian - Ordila Ordila; Shorea Helminasari; Trisna Waty Riza Eryani; Deandlles Christover (Academia Open, 2025)
General Background: Traditional institutions hold a strategic role in maintaining social harmony, preserving cultural values, and resolving disputes in Indonesia, yet their performance is often challenged by modernization and limited institutional resources. Specific Background: In Tanjung Lapang Village, West Malinau District, the Traditional Institution serves as the main actor in the Dayak Lundayeh engagement cancellation custom, covering ceremonial procedures, settlement of legal and social impacts, and dispute mediation, despite facing issues in ensuring process effectiveness and fairness. Knowledge Gap: In-depth empirical studies on the mechanisms, supporting factors, and obstacles of Traditional Institutions in handling engagement cancellations at the village level, particularly in North Kalimantan, remain scarce. Aims: To analyze the performance of the Traditional Institution in implementing the engagement cancellation custom and to identify its supporting and inhibiting factors. Results: This qualitative study found that the Traditional Institution is effective as a facilitator, mediator, and arbitrator, strongly supported by the community, but hindered by limited communication, modernization influences, and resource constraints. Novelty: This study provides a comprehensive empirical account of the dynamics of engagement cancellation in traditional villages and emphasizes the need for institutional adaptation to social change. Implications: Strengthening institutional capacity, enhancing customary law literacy, and fostering cross-sector collaboration are crucial to sustaining the role of the Traditional Institution in preserving cultural values and resolving disputes in Tanjung Lapang Village. Highlights: Highlights the central role of traditional institutions in engagement cancellation customs. Identifies key challenges including modernization and limited resources. Recommends capacity building and cross-sector collaboration for sustainability. Keywords: Traditional Institution, Engagement Cancellation, Dispute Resolution, Local Wisdom